Characteristics of Bromelain enzyme from Queen variety pineapple crown at different drying temperatures. Issue 1 (1st June 2022) - Susanti, S; Rizqiati, H; Pratama, Y; Arifan, F; Reza, S P
Abstract: Pineapple ( Ananas comosus (L) Merr) is a plant that contains bromelain enzymes in almost all parts of the plant, such as fruit, leaves, crown, and the stem with different amounts. Bromelain is included in the protease enzyme group that can break down the molecular structure of proteins into amino acids. Pineapple crown is one of the waste products from pineapple processing that has not been used optimally. This study aims to utilise Queen pineapple crown waste and determine the characteristics of Queen pineapple crown bromelain enzymes which consist of protein content, unit activity, and specific activity at different drying temperatures. Queen pineapple crowns were dried using a cabinet dryer at the temperature of 35°C, 40°C, 45°C, and 50°C before the extraction process. The optimum temperature in the Queen pineapple crowns drying process to produce bromelain with a protein content of 4.41 mg/ml, unit activity 1.36 U/ml, and specific activity 0.31 U/ml was 40°C, then purified by adding 20%, 40%, 60%, and 80% ammonium sulfate. The optimum concentration of ammonium sulfate used to produce pure bromelain (0.33 U/mg specific activity) from Queen pineapple crowns was 60%.